Systemic administration of PTH supports vascularization in segmental bone defects filled with ceramic-based bone graft substitute - Freischmidt, Holger; Armbruster, Jonas; Bonner, Emma; Gühring, Thorsten; Nurjadi, Dennis; Bechberger, Maren; Sonntag, Robert; Schmidmaier, Gerhard; Grützner, Paul Alfred; Helbig, Lars (Cells, 2021)
Non-unions continue to present a challenge to trauma surgeons, as current treatment options are limited, duration of treatment is long, and the outcome often unsatisfactory. Additionally, standard treatment with autologous bone grafts is associated with comorbidity at the donor site. Therefore, alternatives to autologous bone grafts and further therapeutic strategies to improve on the outcome and reduce cost for care providers are desirable. In this study in Sprague-Dawley rats we employed a recently established sequential defect model, which provides a platform to test new potential therapeutic strategies on non-unions while gaining mechanistic insight into their actions. The effects of a combinatorial treatment of a bone graft substitute (HACaS+G) implantation and systemic PTH administration was assessed by mu-CT, histological analysis, and bio-mechanical testing and compared to monotreatment and controls. Although neither PTH alone nor the combination of a bone graft substitute and PTH led to the formation of a stable union, our data demonstrate a clear osteoinductive and osteoconductive effect of the bone graft substitute. Additionally, PTH administration was shown to induce vascularization, both as a single adjuvant treatment and in combination with the bone graft substitute. Thus, systemic PTH administration is a potential synergistic co-treatment to bone graft substitutes.